Series 14 - Ep 19: Goat farming, financial literacy, tree and conservation - Burra, Dharani Dhar; Vyas, Shalika; Ramirez Villegas, Julian Armando; Rottmann, S.; Amimo, J. (2024)
"Shamba Shape Up" is a popular television show in East Africa that focuses on agricultural education and improvement. The show features a team of experts who visit different farms, providing practical demonstrations and advice to farmers on various aspects of agriculture, such as livestock management, farm risk management, and sustainable agriculture. It aims to educate and empower farmers with valuable information and skills to enhance productivity, increase yields, and improve their livelihoods. The program combines entertainment with education, using a reality TV format to engage viewers and encourage the adoption of better farming methods. This episode, part of Series 14, focuses on financial literacy, and is funded by the Livestock & Climate (L&C) initiative.